Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1063/1.1851433
|View full text |Cite
|
Sign up to set email alerts
|

A spectroscopic comparison between several high-symmetry S=10 Mn12 single-molecule magnets

Abstract: We report angle-dependent high-field electron-paramagnetic-resonance data collected for single-crystal samples of Mn 12 -Ac. The spectra reveal fine structures associated with various Mn 12 species corresponding to different disordered local environments. Each of the fine structures exhibits a distinct dependence on the field orientation, thereby highlighting the discrete nature of the disorder. We compare these data with the spectra obtained for two recently discovered analogs of Mn 12 -Ac, differing only in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
38
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 13 publications
3
38
1
Order By: Relevance
“…[20][21][22][23][24][25][26] Indeed, single-crystal high-frequency electron paramagnetic resonance ͑HFEPR͒ suggests that ϳ50% of the molecules expe-rience a significant rhombicity, characterized by a secondorder rhombic ZFS parameter E ϳ 0.01 cm 25,26,29 Effects attributed to the disordered acetic acid in 1 were found to be absent in 2 and 3, thus revealing the quantum dynamics of Mn 12 in a truly axially symmetric ͑S 4 ͒ environment for the first time. [25][26][27][28][29][30] Here, we report on a new Mn 12 complex that is still more closely related to the original acetate: ͓Mn 12 O 12 ͑O 2 CCH 3 ͒ 16 ͑CH 3 OH͒ 4 ͔ ·CH 3 OH ͓Mn 12 Ac/ CH 3 OH͑4͔͒. We also explore further the effects of disorder on the quantum dynamics of Mn 12 SMMs by deliberately removing solvent from crystals of the new high-symmetry complexes ͑2-4͒ by drying them under vacuum.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22][23][24][25][26] Indeed, single-crystal high-frequency electron paramagnetic resonance ͑HFEPR͒ suggests that ϳ50% of the molecules expe-rience a significant rhombicity, characterized by a secondorder rhombic ZFS parameter E ϳ 0.01 cm 25,26,29 Effects attributed to the disordered acetic acid in 1 were found to be absent in 2 and 3, thus revealing the quantum dynamics of Mn 12 in a truly axially symmetric ͑S 4 ͒ environment for the first time. [25][26][27][28][29][30] Here, we report on a new Mn 12 complex that is still more closely related to the original acetate: ͓Mn 12 O 12 ͑O 2 CCH 3 ͒ 16 ͑CH 3 OH͒ 4 ͔ ·CH 3 OH ͓Mn 12 Ac/ CH 3 OH͑4͔͒. We also explore further the effects of disorder on the quantum dynamics of Mn 12 SMMs by deliberately removing solvent from crystals of the new high-symmetry complexes ͑2-4͒ by drying them under vacuum.…”
mentioning
confidence: 99%
“…[20][21][22][23][24][25][26] While the average S 4 symmetry allows MQT interactions ͑transverse anisotropy͒ which are fourth order in the spin operators, intrinsic disorder associated with the noncentrosymmetric acetic acid solvent is found to lead to discrete local environments, resulting in a significant fraction of molecules possessing lower than fourfold symmetry. [20][21][22][23][24][25][26] Indeed, single-crystal high-frequency electron paramagnetic resonance ͑HFEPR͒ suggests that ϳ50% of the molecules expe-rience a significant rhombicity, characterized by a secondorder rhombic ZFS parameter E ϳ 0.01 cm 25,26,29 Effects attributed to the disordered acetic acid in 1 were found to be absent in 2 and 3, thus revealing the quantum dynamics of Mn 12 in a truly axially symmetric ͑S 4 ͒ environment for the first time. [25][26][27][28][29][30] Here, we report on a new Mn 12 complex that is still more closely related to the original acetate: ͓Mn 12 O 12 ͑O 2 CCH 3 ͒ 16 ͑CH 3 OH͒ 4 ͔ ·CH 3 OH ͓Mn 12 Ac/ CH 3 OH͑4͔͒.…”
mentioning
confidence: 99%
“…Mn 12 BrAc, 26,44 Mn 12 tBuAc, 36,45,46 and Mn 12 Ac·MeOH, 34 i.e. the acetate crystallized from MeOH solvent instead of acetic acid and water.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, we note that comparable B 4 4 values are found for the SR Mn 12 complexes. 37,[40][41][42][43]45,46 In addition, given the low symmetry of SR Mn 12 and the presence of a very low-lying excited spin state, it is quite reasonable to expect a comparable rhombic 4 th order term. 70 Efforts to obtain improved simulations do not serve any useful purpose, because the applicability of the giant spin description is questionable for a molecule that clearly possesses such a low-lying excited spin multiplet (see Fig.…”
mentioning
confidence: 99%
“…However we have shown that full removal of the acetic acid of crystallisation resolves the disorder in the O atoms of the acetate ligands, producing species that have true, unbroken S 4 symmetry. We expect 2 and 3 to exhibit similar QTM dynamics [32][33][34][35] to other fully axial analogues in the Mn 12 family: Mn 12 -tBuAc and Mn 12 -BrAc. Hence, we are refining the single-crystal to single-crystal method used to produce species 2 and 3, in order that we can selectively produce pure samples of either material for further study.…”
mentioning
confidence: 99%